2020
DOI: 10.21203/rs.3.rs-37468/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term Monitoring of Dynamic Changes in Plasma EBV DNA For Improved Prognosis Prediction of Nasopharyngeal Carcinoma

Abstract: Background: This study was performed to investigate whether long-term monitoring of dynamic changes in plasma Epstein-Barr virus (EBV) DNA could improve prognosis prediction of nasopharyngeal carcinoma (NPC).Methods: 1077 non-metastatic NPC patients were recruited to retrospectively analyze the prognostic value of plasma EBV DNA load pre-treatment and 3, 12, 24, and 36 months post-treatment. We also examined the prognostic value of dynamic changes in plasma EBV DNA at various time points.Results: Patients with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The infection of EBV is common in NPC in endemic areas. The level of plasma EBV DNA has been shown to be the most attractive potential biomarker for predicting the prognosis and providing accurate risk strati cation in NPC [20]. Intriguingly, a recent prospective screening study involving 20174 participants showed that plasma EBV DNA detection was useful for nasopharyngeal carcinoma screening, with 97.1% sensitivity and 98.6% speci city.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of EBV is common in NPC in endemic areas. The level of plasma EBV DNA has been shown to be the most attractive potential biomarker for predicting the prognosis and providing accurate risk strati cation in NPC [20]. Intriguingly, a recent prospective screening study involving 20174 participants showed that plasma EBV DNA detection was useful for nasopharyngeal carcinoma screening, with 97.1% sensitivity and 98.6% speci city.…”
Section: Discussionmentioning
confidence: 99%